ANALISIS EFEKTIVITAS STRATEGI PEMASARAN DIGITAL MELALUI MEDIA SOSIAL DAN MARKETPLACE DALAM MENINGKATKAN PENJUALAN - Sarbia, Suraidah; Ramadan, Khalam (Universitas Ichsan Sidenreng Rappang, 2025)
This statement looks at how digital marketing strategies through social media and marketplaces can increase sales. As more and more people use the internet and digital devices, the business world is starting to change fundamentally. Therefore, digital marketing is an important part that cannot be separated from business success. Social media provides an opportunity to build brand awareness and make customers more loyal, while marketplaces help businesses gain access to a larger market with ready-to-use transaction systems. This research uses a number-based approach by sending questionnaires to business actors who have implemented digital marketing strategies. The data collected will later be analyzed using the linear regression method.